2010
DOI: 10.3344/kjp.2010.23.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Blood Patches in a Patient With Multi-level Cerebrospinal Fluid Leakage That Was Induced by Spontaneous Intracranial Hypotension

Abstract: Spontaneous intracranial hypotension (SIH) is considered to be a very rare disorder. It is characterized by an orthostatic headache that is aggravated with the patient in the upright position and it is relieved by the patient assuming the supine position. SIH is caused by a spontaneous spinal cerebrospinal fluid leakage without the patient having undergone trauma, surgery or dural puncture or having any other significant medical history. An autologous epidural blood patch (EBP) is effective in relieving SIH. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…In the paper, the authors described that they found only one case report where a patient (after identification of CSF leakages) was successfully managed by injecting an EBP under fluoroscopic guidance at the upper cervical and at the middle thoracic level. 2 By citing only this report, however, they overlooked the case description by Feltracco et al 3 who in 2010 reported on: simultaneous EBPs at different intervertebral spaces for SIH.…”
Section: Sirmentioning
confidence: 87%
See 2 more Smart Citations
“…In the paper, the authors described that they found only one case report where a patient (after identification of CSF leakages) was successfully managed by injecting an EBP under fluoroscopic guidance at the upper cervical and at the middle thoracic level. 2 By citing only this report, however, they overlooked the case description by Feltracco et al 3 who in 2010 reported on: simultaneous EBPs at different intervertebral spaces for SIH.…”
Section: Sirmentioning
confidence: 87%
“…We referred in the paper the infrequent use of a double simultaneous EBP for treatment of SIH and the only find by the authors of a case report where this procedure was performed. 2 In that case, they identified cerebrospinal fluid (CSF) leakage (by radionuclide cisternography) at the upper cervical level and at the middle thoracic level, and the patient was successfully managed by injecting the EBP at each level of leakage at the same time. 2 Likewise, we admit we could have overlooked to cite the case reported by Feltracco et al, 3 who described 3 years ago their experience on blind simultaneous EBP.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…To treat refractory cases of SIH, an epidural blood patch (EBP) is a very effective treatment modality. [9][10][11][12][13] Although a targeted EBP seems to be effective, 14,15 some patients need repeated blood patches because of inadequate control of their postural headache. Curious about the reason for the unresponsiveness to the EBP in such patients, we aimed in this study to find the relationship between EBP responses and cisternographic findings, hypothesizing that the number of EBPs would increase if the number of CSF leakage levels in RI cisternography increased.…”
mentioning
confidence: 99%
“…Conservative therapy includes bed rest, hydration and administration of caffeine or steroids . When conservative measures fail, the use of autologous epidural blood patches (EBP) is recommended . Because of the use of a single EBP does not relieve the symptoms in a variable percentage of patients, some of them require 2 or 3 ones .…”
mentioning
confidence: 99%